Attitudes towards insulin pump therapy among adolescents and young people - Seereiner, Sabine; Neeser, Kurt; Weber, Christian; Schreiber, Karsten; Habacher, Wolfgang; Rakovac, Ivo; Beck, Peter; Schmidt, Louise; Pieber, Thomas R (Diabetes technology & therapeutics, 2010)
This study investigated reasons for the rejection and discontinuation of insulin pump therapy and explored general attitudes towards this mode of therapy among young patients with type 1 diabetes. A questionnaire was developed using a focus group of young people with diabetes. It was then used to survey a random sample of adolescents and young people identified by physicians specializing in diabetes care and participating in a voluntary quality improvement initiative in Germany. The physicians were also surveyed. Eighty-eight patients participated in the survey (22 had never used the pump, 20 had formerly used the pump, and 46 were using the pump at that time, with an average age of between 20 and 22 years, depending on the group). Those who had never used the pump had had diabetes for a significantly shorter length of time and had undergone their first diabetes education more recently. Current pump users were significantly younger at the time of the first diabetes education. There were no significant differences between patients concerning where they obtained their information about the condition and treatment options. Although clinical factors were named, social and psychological factors were prominent as reasons both in reluctance to try the pump therapy and in discontinuing therapy. Technical problems as a disadvantage of the pump (aside from the catheter) were less likely to be named. Responses among physicians confirmed discipline and compliance were essential prerequisites for this therapy and supported findings that patients discontinuing pump therapy at their own request tend to do so for nonclinical reasons. Although the technical reliability of the insulin pump was generally accepted by all patients regardless of current treatment, clinical disadvantages relating to the use of the pump but more commonly social/psychological factors were named, which resulted in patients being reluctant to try this therapy or discontinuing use of it.